Peningkatan Kemampuan Menyusun Bahan Ajar Melalui Pembimbingan Berkelanjutan Bagi Guru Madrasah Ibtidaiyah Tamrinussibyan 1 Alhikmah, Benda Kec. Sirampog Kab. Brebes Semeseter II Tahun Pelajaran 2015/2016 - Slamet Slamet (Institut Agama Islam Negeri Purwokerto, 2018)
The purpose of this study is to find out how much improvement of the ability to arrange teaching materials and how high the motivation of composing teaching materials through continuous mentoring for teachers in Madrasah Ibtidaiyah Tamrinussibyan 1 Alhikmah, Benda, District of Sirampog, Brebes Regency in the Second Semester II Lesson of Academic Year 2017/2018. This study aims to describe the ability of teachers in preparing the teaching materials through continuous mentoring and describe the motivation of teachers in preparing the teaching materials with continuous mentoring. Data were collected through observations and interviews conducted 2 cycles. The results of the assessment are as follows: the highest value was 85, the lowest was 65, and average score was 76.5. There was an average increase in the ability of 29.66% of teaching materials in cycle I. In cycle II the average was 87. The highest score was 93 and the lowest score is 83. There was an increase of 13.73% in cycle II. Teacher's motivation improved significantly in cycle I and cycle II. Thus there is an increased ability to prepare teaching materials through continuous mentoring.